Networked ZnO nanosheets produced by automatic SILAR method - Petrushenko, Sergey; Dukarov, Sergey; Sukhov, Volodymyr; Fijalkowski, Mateusz; Klochko, Natalia; Kopach, Volodymyr (IEEE, 2023)
In this work, we have developed an automatic low temperature, cheap, simple and scalable chemical method Successive Ionic Layer Adsorption and Reaction (SILAR) to obtain layers of two-dimensional zinc oxide (ZnO) nanostructures from aqueous solutions. The ZnO networked nanosheets obtained by the automatic SILAR method have high adhesion to the glass substrate and improved mechanical resistance, which was confirmed by scratch adhesion tests performed by applying a progressive load. The value of the normal force Fz = 2.6 N, corresponding to the critical load Lc, for networked ZnO nanosheets is greater than for a conventional array of ZnO nanorods, for which Fz = 2.1 N.
Author Accepted Manuscript
Keywords: NATURAL SCIENCES::Physics::Condensed matter physics::Semiconductor physics; NATURAL SCIENCES::Physics::Condensed matter physics::Surfaces and interfaces